Android Application Based Cardiac Health Monitoring System: Patients with Heart Disease - Rinda Aulia Utami; Fadli Sukandiarsyah; Saputri Novianti Ramadhani; Khalid Mustofa; Muhammad Dedy Pratama; Wira Anggraini; Vera Veriyallia; Nety Eka Jayanti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
A variety of disorders affecting the heart and blood arteries are together referred to as heart disease. These disorders may impair the heart's capacity to pump blood efficiently and may result in major health issues. This smartphone software assists people with heart problems in following their exercise regimens, receiving medication alerts, and maintaining their medical data. Due of its open source nature and ease of use, an Android-based platform was selected. Physicians utilize cellphones as their main source of medical knowledge and education, as well as for information management tools. Mobile phones, however, can also serve as a platform for initiatives aimed at raising the standard of healthcare. This research aims to utilize technology as health monitoring for heart disease in the community, such as reminders to take medication or access to information (with supporting health examination records and medical diagnoses), and it contains reading articles that provide public knowledge about the importance of maintaining heart health and can improve healthy lifestyles. Methods observational study of 20 heart disease patients at the media farma clinic samarinda with the length of research conducted from application development to application trials takes about April-August 2024. This android mobile-based application uses React Native technology, PHP and Mysql. The result show in the an application with features that have been tested by heart patients with a survey that has been tested for validity. The reliability test was indicated by Cronbach’s alpa 0.938> 0.532 which indicates that the instrument is realiable then the ability to use the application is obtained with the results (80%) and the benefits that make it easier for respondents to monitor heart health are obtained (90%). Conclusion this research has successfully created an android-based heart disease health application that can be used by patients or patient companions as a management and accessibility of their health data. With proper integration, this application can be a very useful tool in improving the quality of life and health of users.